1983
DOI: 10.1073/pnas.80.4.1033
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell types and their evolution in the rat mammary gland determined by immunological markers.

Abstract: We have used immunological reagents for characterizing epithelial cell types in the adult rat mammary gland. Some were sera against purified proteins; others were monoclonal antibodies to mammary cells. On the basis of marker distribution we have identified 10 different cell types. We have established the developmental connection between these types by adopting the principle that cells displaying the same markers are directly related to each other. The results concur with those previously obtained by studying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 8 publications
3
24
0
Order By: Relevance
“…The gland consists of at least four recognizable cell types: adipocytes, fibroblasts, myoepithelial, and epithelial. Regional specialization of epithelial types might also distinguish basal from ductal and secretory epithelium (7)(8)(9)(10) differential tissue-specific response of embryonic mammary epithelium to embryonic mesenchyme in homeotypic and heterotypic recombinant organ cultures. When mammary epithelium is combined with mammary mesenchyme, the result is typical monopoidal branching patterns indicative of normal mammary morphogenesis.…”
Section: Mammary Gland Histogenesismentioning
confidence: 99%
“…The gland consists of at least four recognizable cell types: adipocytes, fibroblasts, myoepithelial, and epithelial. Regional specialization of epithelial types might also distinguish basal from ductal and secretory epithelium (7)(8)(9)(10) differential tissue-specific response of embryonic mammary epithelium to embryonic mesenchyme in homeotypic and heterotypic recombinant organ cultures. When mammary epithelium is combined with mammary mesenchyme, the result is typical monopoidal branching patterns indicative of normal mammary morphogenesis.…”
Section: Mammary Gland Histogenesismentioning
confidence: 99%
“…This approach has been used in our laboratory for studying the pathways of cell differentiation in the mammary gland (1). Antibodies to cytokeratins are especially useful in this context because there are many different kinds of cytokeratins, which display considerable cell specificity.…”
mentioning
confidence: 99%
“…For instance, Lane (15) has shown that monoclonal antibodies to cytokeratins from PtK1 cells recognize cells in the rat mammary gland. We have found that one of these antibodies (Le6l) is highly selective for certain cell types (1). By taking advantage of this crossreactivity, we have prepared a set of monoclonal antibodies from mice immunized with total cow muzzle keratin.…”
mentioning
confidence: 99%
“…Later, moderate ductal growth occurs until puberty, when a more pronounced development of the ducts leads to the formation of a ductal tree (2). In cycling virgin mice, the parenchyma consists of a highly organized system of ducts with terminal end-buds that represent the major sites of ductal growth (3)(4)(5) and give rise to alveolar buds (6). Alveolar buds in turn generate alveoli that eventually may secrete milk proteins during pregnancy and lactation (7).…”
mentioning
confidence: 99%